EVALUATION OF THE FAMILY HOPE PROGRAM (PKH) IN OVERCOMING POVERTY IN BONE DISTRICT - Sefika Sefika; Muh Nur Yamin; Andi Cudai Nur; Anisa Fitri (Universitas Negeri Makassar, 2026)
This research aims to determine the Evaluation of the Family Hope Program (PKH) in Overcoming Poverty in Bone Regency. This type of research is descriptive with a qualitative approach. Data were collected through observation, interviews and documentation with data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this study indicate that needs assessment has not been fully effective in identifying community needs accurately. There is a discrepancy between beneficiary data and conditions in the field, which indicates weaknesses in the data updating process. However, the planning of the PKH program in Bone Regency has been quite good, involving various parties and having a structured fund distribution mechanism. Formative evaluation also shows that the implementation of the program is quite good, with structured monitoring and evaluation and efforts to increase public awareness. In terms of impact, the Summative Program shows that the PKH program has a positive impact on Beneficiary Families (KPM), namely helping to meet the basic needs of KPM, improving welfare, and encouraging behavioral changes towards economic independence. Overall, the PKH program in Bone Regency has shown positive results in improving the welfare and economic independence of KPM. However, improvements are needed in the needs assessment process to ensure that the identification of community needs is more accurate and on target and it is recommended that data be updated regularly to avoid discrepancies between beneficiary data and conditions in the field.